(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Expanding trade between India and European Union countries leads to increased EUR/INR transactions which make the currency market more volatile and riskier to trade. Traders and investors who are exposed to currency fluctuations try to hedge their risks by investing in euro futures contracts. In this study, we assess EUR INR spot and futures prices from January 2010 – December 2019 using Grangers causality, Johansen’s cointegration, and VECM techniques. Stationarity of employed dataset is confirmed using ADF test. Existence of long run equilibrium between euro-rupee futures and spot market and at least one cointegrating vector is confirmed using Johansen’s cointegration. The Granger causality results signify one-way causality betwixt the price series where, futures prices lead spot prices. The ECT is considered to be significant. Thus, we conclude that the euro futures market at National Stock Exchange (NSE) is efficient and performs price discovery function. Traders, retail investors, policy makers and mutual fund managers who diversify their investments can advance from this study.